The Influence on Hydrodynamic Drag of High Molecular Weight Compounds in the Turbulent Boundary Layer - Smallman, John R. (My University, 1967)
This thesis describes in detail an experimental study made into the evaluation and explanation of the reduction in hydrodynamic drag resulting from the addition of small proportions of certain water soluble polymers to distilled water.
An experimental apparatus was designed which would, it was hoped, yield repeatable results. This apparatus consisted basically of a chamber which was filled with the test fluid, and which contained a rotating disk whose speed could be varied and whose torque could be measured.
To develop a theory which would explain this reduction in hydrodynamic drag a boundary layer velocity profile was determined for pure water at a given disk radius, and then for water containing the long chain polymer "polyacrylamide MRL-159". These two velocity profiles were determined using a special velocity probe developed for the purpose; and hence a section of this thesis will describe in detail its development and operation.
All solution concentrations alluded to in the text, in the tabular and graphical presentations, and in the calculations are in parts of solute per million parts of solvent (P.P.M.), by weight.
The weights of the solutes used in the determination of concentrations were corrected for moisture content as determined in oven drying procedures fully described in section 4.2 entitled "Stock Preparation and Control".
Title: The Influence on Hydrodynamic Drag of High Molecular Weight Compounds in the Turbulent Boundary Layer, Author: John R. Smallman, Location: Thode